Amish Femininity: New Lessons from the Old Order - Jolly, Natalie (Journal of the Motherhood Initiative for Research and Community Involvement, 2015)
I consider how a woman is expected to do gender may influence how she is expected todo birth. I ask how mainstream norms of femininity, particularly those that celebratepassivity and weakness, manifest in a woman’s particular experience of childbirth.As a counterpoint, I examine how gender norms associated with Amish femininityshape Amish women’s experience of birth. I present an ethnographic account of threeaspects of Old Order Amish birth based on the criteria developed by Sarah Jane Brubakerand Heather Dillaway and consider (1) details of the birth setting, (2) issuesof control, and (3) how the use of medical technology (or lack thereof ) may be seen toinfluence a woman’s birth experience. I draw on two years of participant-observerdata to show how practices such as midwife-attended unmedicated homebirth come topossess specific social meaning for Amish women, and are tied to how Amish womendo gender. I conclude by suggesting that a discourse of femininity valuing hard work,body confidence, and shared power constructs an environment where the work of laboris equated with accomplishment rather than something distasteful to be avoided, andmay create a social context within which women can do birth differently.